Enantioselective Synthesis of Antiepileptic Drug: (-)-Levetiracetam—Synthetic Applications of the Versatile New Chiral N-Sulfinimine - K. Chandra Babu; R. Buchi Reddy; E. Naresh; K. Ram Mohan; G. Madhusudhan; K. Mukkanti (Journal of Chemistry)
We report an asymmetric synthesis of (-)-Levetiracetam (1) in six steps starting from versatile new chiral N-sulfinimine (3). The key step, stereoselective 1,2-addition of ethylmagnesium bromide (EtMgBr) to chiral N-sulfinimine derived from (R)-glyceraldehyde acetonide and (S)-t-BSA, gave the corresponding sulfonamide (2) in high diastereoselectivity. Simultaneous deprotection and deacetylation followed by NaIO4 cleavage and reduction gave β-amino alcohol (6). Subsequent reactions yielded the targeted compound levetiracetam (1).